A case of ganglioglioma grade 3 with H3 K27M mutation arising in the medial temporal lobe in an elderly patient. Issue 3 (20th February 2022) - Fujii, Yutaro; Hatae, Ryusuke; Hata, Nobuhiro; Suzuki, Satoshi O.; Sangatsuda, Yuhei; Takigawa, Kosuke; Funakoshi, Yusuke; Fujioka, Yutaka; Kuga, Daisuke; Mizoguchi, Masahiro; Iwaki, Toru; Yoshimoto, Koji
Abstract : The mutation p.K27M in H3F3A ( H3 K27M mutation) is mainly detected in diffuse midline glioma. However, recent studies have demonstrated that H3 K27M mutation could also be observed in a subset of gangliogliomas. Importantly, most H3 K27‐mutated ganglioglioma cases also harbor BRAF V600E mutation. Herein, we report a rare case of H3 K27M‐mutated ganglioglioma grade 3 without BRAF mutation arising in the medial temporal lobe in an elderly man. A small biopsy specimen was sampled. The pathological diagnosis was diffuse astrocytoma. The tumor progressed gradually during an 18‐month follow‐up period. Gadolinium enhancement on magnetic resonance imaging was noted 36 months after the biopsy. The patient was referred to a hospital for tumor resection. Histological analysis of resected specimens led to a diagnosis of ganglioglioma grade 3 with H3 K27M mutation. The patient underwent concurrent temozolomide chemotherapy with radiotherapy. Although the patient's condition deteriorated after chemotherapy due to disease progression, he survived for more than 23 months after tumor resection. We present this rare case and discuss the involvement of H3 K27M mutation in ganglioglioma grade 3.